1986
DOI: 10.3109/17453678609014782
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic hemarthrosis in stable knees

Abstract: A thorough arthroscopic examination was performed in 90 consecutive patients with sprained knee injuries with hemarthrosis, but without signs of instability or fracture. The source of bleeding was found in all but five joints. Thirty-nine injuries were tears of the cruciate ligament, only three of which were complete tears. Fourteen injuries were (osteo)chondral fractures and six were meniscal lesions. The remainder bled from the synovium or meniscal attachments. The arthroscopic examination resulted in an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Twenty five per cent of all severe ligament and capsular knee injuries in young patients (aged 15 to 55 years), resulting in swelling of the knee, are associated with articular cartilage damage 78. One study has shown that of 31,516 knee arthroscopic procedures, in patients with a mean age of 43 years (range 1 year to 92 years), 63% were shown to have damage of the cartilage lining the knee when assessed by the International Cartilage Repair Society (ICRS) knee evaluation criteria 7.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty five per cent of all severe ligament and capsular knee injuries in young patients (aged 15 to 55 years), resulting in swelling of the knee, are associated with articular cartilage damage 78. One study has shown that of 31,516 knee arthroscopic procedures, in patients with a mean age of 43 years (range 1 year to 92 years), 63% were shown to have damage of the cartilage lining the knee when assessed by the International Cartilage Repair Society (ICRS) knee evaluation criteria 7.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly a quarter of all severe ligament or capsular knee injuries that result in a haemarthrosis are associated with cartilage damage 1 2. Breakdown of the cartilage from trauma or disease results in severe pain and disability and may progress to early osteoarthritis.…”
mentioning
confidence: 99%